Infantile multiple large pyogenic granuloma on burned skin. Case report and review of literature - Ladan Dastgheib; Zohreh Maghami; Fatemeh Sari Aslani (Anais Brasileiros de Dermatologia, 2016)
Abstract Pyogenic granuloma (PG) is a benign vascular lesion of the skin and mucous membranes, presenting as a solitary, red, pedunculated papule that bleeds easily and which appears to be a reactive vascular proliferation to minor injury. These lesions are more common in children and are mostly seen in exposed sites. Multiple disseminated PG is a rare condition. This report describes an infant with multiple, disseminated, pyogenic granulomas following burns from boiling milk. We reviewed literature published in English and found 9 cases. Six cases were provoked by hot milk, 2 by hot water, while the cause of the other case is unknown. Angiogiogenetic activity in milk may explain PG development in these patients.